Gambaran Persepsi Ibu Hamil tentang Hubungan Seksual Selama Kehamilan - Novita Wulandari; Yayuk Eliyana (SAKTI BIDADARI (Satuan Bakti Bidan Untuk Negeri), 2022)
Pregnancy is a series in a series that starts from conception, nidation, introduction of maternal adaptation to nidasi, pregnancy maintenance, endocrine changes in preparation for the birth of the baby and childbirth with readiness to care for the baby. Based on the results of the initial survey it is known that from 10 people as many as 7 (70%) pregnant women do not have sexual intercourse for fear of harming the fetus. The purpose of the study was to find out the picture of pregnant women's perceptions of sexual intercourse during pregnancy. This type of research is descriptive with the population of all pregnant women in The Third Trimester in Polindes Candi Burung Subdistrict Proppo as many as 40 pregnant women. Based on the way of data collection there is a type of research that is survey research. TM III pregnant women's perception of sexual intercourse variables during pregnancy. Data collection instruments use questionnaires. From the results of the analysis of univariate data obtained research data that from 40 pregnant women almost entirely in the polyndes bird temple (95%) negatively perceived. Solutions that can be done to overcome negative perceptions. Pregnant women should seek information especially about sexual relations during pregnancy from print, electronic, or continuous counseling. About the benefits that will be obtained in sexual intercourse during pregnancy.